“YOUTH CREATIVE ENTERPRENEUR EMPOWERMENT (YOUTIVEE)”: Solutions for Youth to Contribute to the Economy and Reduce Unemployment - Fattah, Anim; Syairozi, Muhamad Imam; Rohimah, Lailatur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Youth Creative Entrepreneur Empowerment (YoutivEE), a program to empower young people to contribute to the economy and reduce unemployment . YoutivEE is an empowerment program that can be implemented by the government, the private sector or even the youth themselves. Viewed from the Bali Sustainable Creative Supply Chain Industry, YoutivEE is a program intended for students at public and private universities. YoutivEE aims to prepare students with all soft skills and hard skills before entering the creative industry and later being able to contribute to empowering the surrounding community. YoutivEE is sustainable, YoutivEE at the university level will be followed by YoutivEE at the city level (city based). YoutivEE will be directly mentored by people who are experienced in their fields and mentored specifically step by step